Accounting for the Environmental Impacts of Cement Production on Host Communities: A Case Study of Ewekoro, Nigeria (Global Journal of Management and Business Research, 2019)
The contribution of manufacturing sector of the Nigerian economy cannot be ignored and cement production occupies a notable position in this sector. The cement industry of the manufacturing sector contributes to the growth of the economy through its sales and distribution chain, job creation, monetary circulation and lots more. However, the production process has both economic and environmental impacts on host communities as raw materials are continuously drawn-up to keep production functioning and toxic waste material are released back into the natural environment. This paper examines the environmental and economic impact of cement production of Lafarge WAPCO on local inhabitants of Ewekoro Local Government Area, Nigeria using descriptive survey design and data collected with the aid of a close ended questionnaire and scheduled interview with households.
Keywords: environmental impacts; cement production; pollution; toxic waste; economic effect